FATIGUE PROPERTIES OF MACHINED SPECIMENS FROM CAST AND FORGED RAILROAD WHEELS - Queiroz, Syme R. S.; Minicucci, D.; Boas, R. V.; Guimaraes, V.; Ferreira, I. [UNESP]; SilvaGomes, J. F.; Vaz, MAP (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2012)
The worldwide tendency of railways is the high load per wagon in cargo transport and high speed in the passenger sector. In both situation the wheel is strongly required, especially in respect of fatigue, which have being the mainly cause in accidents having wheel failure or bring the wheel out of service before end of its life. This research shows the comparison between the fatigue properties of forged and cast wheels. The research indicates what type of wheel is more resistant to fatigue taking account the test conditions.
Keywords: Wheel; fatigue; mechanical properties; fatigue properties